Pengaruh Influencer Saham Terhadap Minat Investasi Generasi Milenial Pada Pasar Modal - Tasha Indy Regita (Fakultas Ekonomi Universitas Kadiri, 2022)
Technological developments have an impact on various sectors. The marketing sector is one of them, the use of social media in marketing comes the term stock influencer. A stock influencer is a celebrity or person with a large following on social media who frequently shares information about stocks. The purpose of this study is to determine the influence of stock influencers on millennial generation's investment interest in the capital market by using references sourced from scientific articles and then analyzing them to solve problems. The existence of stock influencers provides a positive value in influencing the millennial generation to invest in the capital market.